Guide to computer network security - Kizza, Joseph Migga (Computer communications and networks., 2013)
This book explores security risks and vulnerabilities of computer networks and networked devices, offering improved algorithms and best practices for enhancing system security. This revised, updated edition encompasses agile mobile systems and social networks.